Exploration of Factors Predictors Nurses’ Occupational Stress on Facing Covid-19 Pandemic - Rizqi Wahyu Hidayati; Novita Nirmalasari; Ike Wuri Winahyu Sari (Disease Prevention and Public Health Journal, 2023)
Background: The fluctuating wave of Covid-19 cases induced the nurses’ work pressure, both physical and psychological. Occupational stress and burnout were caused by a nursing care plan, moving the nursing and health equipment. It influences decreasing in nursing care, working motivation, and patient safety, such as falls and medication errors. This study aimed to evaluate the factors influencing nurses' occupational stress in facing Covid-19 Pandemic in Yogyakarta. Method: The mixed method was used in this study. Using convenience sampling, 272 nurses who work at the Covid-19 hospital in Yogyakarta. The inclusion criteria were registered as Indonesian Nurses; with one-year experience of in work. The Nurses Occupational-Stress Scale 21 (NOSS-21) and Family Support Scale (FSS) were used to evaluate the nurses’ occupational stress and the family support system. It was analyzed using binary logistics. Results: The nurses' occupational stress showed a mean score of 44.40 ± 9.077. This score indicated low nurses' occupational stress. Age and nurses’ position had statistically significant positive effects on nurses' occupational stress (β = 6.305; p = 0.00) and (β = 0.469; p = 0.021). Conclusion: The nurses' occupational stress is related to the nurses' ages and position in the area of their work at a hospital.